Micro-organisms attached to the lumens and balloons of indwelling urinary catheters and correlation with symptoms, antibiotic use and catheter specimen of urine results. Issue 4 (26th February 2019) - Belfield, Katherine; Kalith, Sajitha; Aimar, Kelsey; Parkinson, Richard; Bayston, Roger
Abstract : To determine micro-organisms attached to removed urethral catheters and relate this to patient-specific information. Indwelling urethral catheters were collected from patients at a UK teaching hospital. The balloon and lumen were sonicated, and micro-organisms were enumerated. Catheter specimen urine results were retrospectively reviewed. Escherichia coli and Enterococcus faecalis were the most common isolates from 61 catheters. 19.7% of patients received antibiotics and 25 % of those had a multi-drug-resistant (MDR) organism in the lumen. Only 2.04% of catheters from patients not receiving antibiotics had a MDR organism. All lumens were colonized irrespective of antibiotic use. Symptom presentation did not correlate with numbers of colonizing organisms or species. Despite heavy colonization, only 8/61 patients were symptomatic. Indwelling urinary catheters in place for ≥10 days were universally colonized and there was no correlation with symptom presentation. Symptom presentation remains the most important factor for defining catheter-associated urinary tract infection.